Defining tumor resistance to PD-1 pathway blockade: recommendations from the first meeting of the SITC Immunotherapy Resistance Taskforce. Issue 1 (1st April 2020) - Kluger, Harriet M.; Tawbi, Hussein A.; Ascierto, Maria L.; Bowden, Michaela; Callahan, Margaret K.; Cha, Edward; Chen, Helen X.; Drake, Charles G.; Feltquate, David M.; Ferris, Robert L.; Gulley, James L.; Gupta, Shilpa; et al.
Abstract : As the field of cancer immunotherapy continues to advance at a fast pace, treatment approaches and drug development are evolving rapidly to maximize patient benefit. New agents are commonly evaluated for activity in patients who had previously received a programmed death receptor 1 (PD-1)/programmed death-ligand 1 (PD-L1) inhibitor as standard of care or in an investigational study. However, because of the kinetics and patterns of response to PD-1/PD-L1 blockade, and the lack of consistency in the clinical definitions of resistance to therapy, the design of clinical trials of new agents and interpretation of results remains an important challenge. To address this unmet need, the Society for Immunotherapy of Cancer convened a multistakeholder taskforce—consisting of experts in cancer immunotherapy from academia, industry, and government—to generate consensus clinical definitions for resistance to PD-(L)1 inhibitors in three distinct scenarios: primary resistance, secondary resistance, and progression after treatment discontinuation. The taskforce generated consensus on several key issues such as the timeframes that delineate each type of resistance, the necessity for confirmatory scans, and identified caveats for each specific resistance classification. The goal of this effort is to provide guidance for clinical trial design and to support analyses of emerging molecular and cellular data surrounding mechanisms of resistance.